Iron-catalyzed Csp3Csp3 bond formation via dehydrative cross coupling reaction: Facile access to new hybrid dihydroquinazolines having quinoline, isoquinoline, quinoxaline and azoles. Issue 15 (12th April 2017) - Srinivasulu, A.; Shantharjun, B.; Kumar, R. Arun; Reddy, K. Rajender
Graphical abstract: Highlights: Demonstrated Csp3 Csp3 bond formation by dehydrative coupling using cheap iron catalyst. Synthesis of hybrid dihydroquinazolines having quinoline, isoquinoline, quinoxaline and azole has been achieved. This method generates water as one of the by-products. This protocol extended to couple acetophenones. Mechanism involves in situ generation of iminium ion followed by attack of carbon nucleophile. Abstract: An operationally simple, efficient and straight forward approach was developed for the synthesis of new hybrid nitrogen heterocycles bearing dihydroquinazoline with quinoline, isoquinoline, quinoxaline and azole via iron-catalyzed dehydrative cross coupling reaction between heterocyclic aminol and 2-methyl azaarenes. Furthermore, this protocol applied to couple simple methyl ketones to achieve C4-alkylated-dihydroquinazolines with broad substrate scope.